1991
DOI: 10.1002/cne.903070310
|View full text |Cite
|
Sign up to set email alerts
|

Active zone organization and vesicle content scale with bouton size at a vertebrate central synapse

Abstract: A common observation in studies of neuronal structure is that axons differ in the size of their synaptic boutons. The significance of this size variation is unclear, in part because we do not know how the size of synaptic boutons is related to their internal organization. The present study has addressed this issue by using three-dimensional reconstruction of serial thin sections to examine the ultrastructure of synaptic boutons that vary in size. Our observations are based on complete or near-complete reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 57 publications
1
39
2
Order By: Relevance
“…There are good reasons to believe that such set points are dictated, at least in part, by AZ size, or, more specifically, by CAZ size. As mentioned above, strong relationships between AZ and various SV pool sizes have been reported (Yeow and Peterson, 1991;Pierce and Mendell, 1993;Stevens, 1997, 1999;Murthy et al, 2001). Our findings that prolonged stimulation paradigms do not affect the synaptic contents of Bassoon are in line with this idea, as they indicate that the AZ, by remaining "indifferent" to the intense dynamics associated with SV recycling, represents a relatively stable nucleus that could impose a particular set point in terms of SV pool size.…”
Section: Use Dependence Of Presynaptic Tenacitymentioning
confidence: 69%
See 1 more Smart Citation
“…There are good reasons to believe that such set points are dictated, at least in part, by AZ size, or, more specifically, by CAZ size. As mentioned above, strong relationships between AZ and various SV pool sizes have been reported (Yeow and Peterson, 1991;Pierce and Mendell, 1993;Stevens, 1997, 1999;Murthy et al, 2001). Our findings that prolonged stimulation paradigms do not affect the synaptic contents of Bassoon are in line with this idea, as they indicate that the AZ, by remaining "indifferent" to the intense dynamics associated with SV recycling, represents a relatively stable nucleus that could impose a particular set point in terms of SV pool size.…”
Section: Use Dependence Of Presynaptic Tenacitymentioning
confidence: 69%
“…One possibility is that such set points are determined by relatively stable molecular complexes found at active zones (AZs), namely, the cytoskeleton of the active zone (CAZ) (Schoch and Gundelfinger, 2006;Sigrist and Schmitz, 2011). Indeed, there seems to be an excellent correlation between AZ size and total (Yeow and Peterson, 1991;Pierce and Mendell, 1993), docked Stevens, 1997, 1999;Murthy et al, 2001), and readily releasable (Matz et al, 2010) SV pool sizes. Following this line of reasoning, the gradual convergence of SI decay rates in stimulated preparations to those measured in nonstimulated preparations might indicate that CAZ remodeling is not strongly affected by the activity regimes tested here, and consequently, following the cessation of stimulation, SVs gradually redistribute among synapses until SV pool sizes once again match the sizes of their respective CAZ.…”
Section: Stimulation Leads To the Partial Dispersion Of Egfp:sv2a Punctamentioning
confidence: 99%
“…As Yeow and Peterson (1991) first noted, active zones rarely exceed an area of 0.4 m 2 (as if larger active zones will not f unction properly), so larger boutons seem to add more active zones to conform to the linear active zone area per bouton volume relationship without exceeding the upper limit for active zone size. As first reported by Hamos et al (1987) and confirmed by the subsequent workers on various synapse types (Streichert and Sargent, 1989;Yeow and Peterson, 1991;Pierce and Mendell, 1993), the number of active zones is linearly related to bouton volume. Again, because hippocampal boutons are small, one would expect to find, as we do, only a single active zone per bouton if the linear active zone area per bouton volume relationship extends to cortical neurons.…”
Section: Comparison With Previous Anatomical Studiesmentioning
confidence: 91%
“…For frog cardiac autonomic synapses (Streichert and Sargent, 1989), turtle spinal cord synapses on motoneurons (Yeow and Peterson, 1991), and 1A synapses on mammalian spinal motoneurons (Pierce and Mendell, 1993), a linear relationship is reported between bouton volume and both the total number of synaptic vesicles and the active zone area. Also, spinal synapses exhibit a skewed distribution of active zone areas with a shape much like the one presented in Figure 4 A, although the active zone areas of the spinal synapses are two and one-half (mammalian) to four (turtle) times those we find in hippocampus.…”
Section: Comparison With Previous Anatomical Studiesmentioning
confidence: 92%
See 1 more Smart Citation